Study of Medication Error in Hospitalised Patients in Tertiary Care Hospital - Patel, Sandip; Patel, Ashita; Patel, Varsha; Solanki, Nilay (Indian Journal of Pharmacy Practice)
AIM: The aim of the present investigation is to study the incidence medication error (ME) in hospitalized patients in a tertiary care hospital. Further, the study was aimed to categorize medication error in the hospitalized patients of surgery and general medicine wards of tertiary care hospital. Method: A prospective observational study of seven months was conducted in the department of surgery ward and general medicine ward at Jivraj Mehta Smarak and Health Foundation. Data were collected using structured data collection form. Major Findings are recorded for the demographic details, drug details and criteria for identifying errors and their categorization, details of drugs involved in errors and rationality of prescription. Result: The study was conducted in 427 patients, where 231 were males (54%) and 196 were females (46%). Out of 427 cases, MEs has detected in 196 cases (45.90%). Most of the medication errors were observed in the age group of 41-60 years (34.69%). Reported incidences of MEs, 99 (51%) and 97(49%) were observed in surgery and general medicine department, respectively. The most frequent error was prescription errors (138; 70.40%) followed by administration errors (58; 29.59%). A potential drug interactions were observed in 95 cases (48%) and serious drug interactions in 28 cases (14%). Majority prescriptions were semi-rational (178; 41.68%) followed by irrational (96; 22.48%) and rational (135; 31.61%). On the evaluation of severity, majority of MEs were category C (118; 60%) followed by category B (44; 22%) and category A (34; 17%). Majority of MEs were belonging to cardiovascular drugs (23; 23%) in medicine ward and gastrointestinal drugs (29; 29%) in surgery ward. Conclusion: The study helps to assess the incidence of medication error and to categorize medication error. In the general medicine department, the majority of patients were geriatrics who are more prone to errors, thus guidelines for safe use of medications in geriatrics should be strictly implemented to prevent medication errors. Antimicrobials are the major class of drugs involved in medication errors, thus this study recommends strict implementations of antibiotic policy in the hospital.
Keywords: Drug -drug interactions; Medication Errors; Prescribing Error; Administration error.